Svay : a Khmer village in Cambodia - Ebihara, May (Southeast Asia Program Publications, an imprint of Cornell University Press, 2018)
"May Mayko Ebihara (1934-2005) was the first American anthropologist to conduct ethnographic research in Cambodia. Provides a remarkably detailed picture of individual villagers and of Khmer social structure and kinship, agriculture, politics, and religion. The world Ebihara described would soon be shattered by Pol Pot's Khmer Rouge. Fifty percent of the villagers perished in the reign of terror, including those who had been Ebihara's adoptive parents and grandparents during her fieldwork. Never before published as a book, Ebihara's dissertation served as the foundation for much of our subsequent understanding of Cambodian history, society, and politics"--